Medicalization and overdiagnosis: different but alike - Hofmann, Bjørn (Medicine, health care, and philosophy, 2016)
Medicalization is frequently defined as a process by which some non-medical aspects of human life become to be considered as medical problems. Overdiagnosis, on the other hand, is most often defined as diagnosing a biomedical condition that in the absence of testing would not cause symptoms or death in the person’s lifetime. Medicalization and overdiagnosis are related concepts as both expand the extension of the concept of disease. They are both often used normatively to critique unwarranted or contested expansion of medicine and to address health services that are considered to be unnecessary, futile, or even harmful. However, there are important differences between the concepts, as not all cases of overdiagnosis are medicalizations and not all cases of medicalizations are overdiagnosis. The objective of this article is to clarify the differences between medicalization and overdiagnosis. It will demonstrate how the subject matter of medicalization traditionally has been non-medical (social or cultural everyday life) phenomena, while the subject matter of overdiagnosis has been biological or biomolecular conditions or processes acknowledged being potentially harmful. They also refer to different types of uncertainty: medicalization is concerned with indeterminacy, while overdiagnosis is concerned with lack of prognostic knowledge. Medicalization is dealing with sickness (sick role) while overdiagnosis with disease . Despite these differences, medicalization and overdiagnosis are becoming more alike. Medicalization is expanding, encompassing the more “technical” aspects of overdiagnosis, while overdiagnosis is becoming more ideologized. Moreover, with new trends in modern medicine, such as P4 (preventive, predictive, personal, and participatory) medicine, medicalization will become all-encompassing, while overdiagnosis more or less may dissolve. In the end they may converge in some total “iatrogenization.” In doing so, the concepts may lose their precision and critical sting.